Penguatan Nilai Karakter Serta Pembentukan Pendidikan Humanistik Melalui Penanaman Mindset Antikorupsi Sebagai Upaya Pencegahan Dan Pemberantasan Korupsi - Ni Made Sulistia Dwi Pradnyamita (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
In Indonesia, it can be said that the eradication of corruption itself has not been optimal, given that there are still many cases of corruption committed by high-ranking state officials that are increasingly being reported in the Indonesian mass media. The effort to eradicate corruption itself is still focused on repression or prosecution which is considered ineffective considering that corruption itself that occurs in Indonesia is already entrenched and rooted in the personalities of the Indonesian people. In its development, anti-corruption education itself has a very important role in solving current corruption problems, it can be seen directly what is happening in the real life of the community that acts of corruption are still very much developing which this phenomenon must be immediately eliminated and eradicated in the life of Indonesian society. This anti-corruption education as a character formation which emphasizes the free will through the potential of students where the results to be implemented in this anti-corruption education are called character building which includes humanism, knowledge about corruption, and how students' attitudes towards the condition of the nation state at the moment.